Faktor Faktor Yang Mempengaruhi Kehamilan Pada Remaja Di Bidan Praktik Mandiri Bidan Ganik, STr.Keb Kota Bogor Tahun 2023 - Yusnia, Nina; Adisti, Amanda Putri; Maryam, Argya Kalyca (Jurnal Kesehatan, 2024)
The WHO maternal mortality rate (MMR) was high in 2020, with 95% occurring in low-income countries. In Indonesia, 4.627 maternal deaths were recorded. Factors such as early marriage, low education, and low economic status affect teenage pregnancy. Knowledge, education, and economic factors contribute to teenage pregnancy. This study is a quantitative study with an analytic descriptive survey method that aims to determine the factors that influence pregnancy in teenagers. The sample uses non-probability techniques, namely saturated sampling of 60 people. The data collection technique used was secondary data obtained from questionnaire data. Univariate results from the survey showed that most respondents had good knowledge (61.7%), poor economy (60%), good culture (86.7%), good peers (63.3%), healthy association (60%), and prefer electronic media (93.3%) compared to printed media. The bivariate study showed an association between peers and teenage pregnancy with a p-value of 0.02 > 0.05, while other variables did not show a significant association.